Ответы и объяснения

2014-03-04T08:29:33+00:00
19.а) (sina-cosa)^2+2sinacosa=sina^2-2sina cosa+cosa^2+2sina cosa =sina^2+cosa^2=1
20. а)(1-сosa)(1+cosa)/sina=1-cos^2/sin=sin^2/sin=
21.   а)  1+tg^2a=1/сos^2a
         1/сos^2a=1/сos^2a
       б) 1/сos^2a-1=tg^2a
           1/сos^2a=1+tg^2a
           1/сos^2a=1/сos^2a
22. cos^2a/1-sina-sina=1
     cosa - cos2a -1)/(sina - 2*sina*cosa) = cosa/sina 
     (cosa - cos2a - 1)/(1 - 2*cosa) = cosa 
     (cosa - 2*cos^2a -1 -1)/(1-2*cosa) = cosa 
     (1-2*cosa)/(1-2*cosa) = 1

23. а) 6sin30*cos30/cos^2 30-sin^2 30=3sin60/(cos^2 30-sin^2 30)=3*корень3
     б)1-2sin^2 60/2sin^2 60-1=
-(1-2sin^2 60)/(1-2sin^2 60)=-1